PELAKSANAAN TUGAS WAITERS DI FRESQA BISTRO BATIQA HOTEL PEKANBARU - Mirna Siska Sari; Siti Sofro Sidiq (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
This study aims to find out the implementation of the duties of waitress in the fresqa bistro of Batiqa Hotel Pekanbaru which consists of seven dimensions namely preparing at the restaurant, receiving and greeting each guest arrival at the restaurant, delivering and finding seating according to their wishes, presenting a list of food, greeting guests, noting guests irregularities / dissatisfaction. The research method used in this research is descriptive quantitative method. The population of this study were all guests of the food and beverage service department at Batiqa Hotel Pekanbaru. In this study the researchers took the number of samples as many as 100 orang. Data collection techniques in this study used observations, questionnaires, and documentation.Based on the research conducted, the results of data processing indicate the level of guest satisfaction with the waiter service at Batiqa Hotel is very high. This can be seen from the total acquisition of the scores of all sub-variables totaling 6089 with very good categories. Keywords: Guest responses, Waiter, F & B Service.